If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.25(y + -1b) = m Reorder the terms: 0.25(-1b + y) = m (-1b * 0.25 + y * 0.25) = m (-0.25b + 0.25y) = m Solving -0.25b + 0.25y = m Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-0.25y' to each side of the equation. -0.25b + 0.25y + -0.25y = m + -0.25y Combine like terms: 0.25y + -0.25y = 0.00 -0.25b + 0.00 = m + -0.25y -0.25b = m + -0.25y Divide each side by '-0.25'. b = -4m + y Simplifying b = -4m + y
| 2+x+3x=46 | | -42=-2a-3(-4a+4) | | 2+3x=46 | | x/5-x/2=3 | | 20-5(x-3)=5+3x | | 2x+2=x+1.2 | | 9x^2+30=-25 | | 3x+2+x=46 | | (y^2)-x+9y-25=0 | | -4+4x=12 | | 5x/4+1/2=x-1/2 | | 10-3(x+2)=3-2x | | 4t-22=30 | | t^3-9t^2=0 | | 22-5n^12=22+15n^13 | | ln(x+6)+ln(4)=ln(10) | | 6y^2+13y-5=0 | | 4-6p-2p=3 | | 2(13t-15)+3(t-19)=0 | | 4x-10+2x=3(5x-5)+2 | | x=-9x^2+x+10 | | -2(2+x)=7(-3x-1) | | -25+10c^2=c^2 | | 3x+2.6=x+24 | | 5+6(-1)= | | 2h^2-7h-1= | | 15x-6.3=0 | | g^2+3g= | | 4t^2+8t= | | -7(x-1)=-4(x+7) | | -2x+7=9x+3 | | 5+6z= |